The Culture of Fear and Control in Costa Rica (I): Crime Statistics and Law Enforcement - Sebastian Huhn (German Institute of Global and Area Studies (GIGA), 2009)
The Costa Rican talk of crime is fundamentally based on the assumption that crime rates have increased significantly in recent years and that there is today a vast and alarming amount of crime. On the basis of this assumption, fear of crime, the call for the 'iron fist', and drastic law enforcement actions are continually increasing. While crime statistics are the logical basis for the hypothesis on the far-reaching extent of delinquency, they are used in a problematic way in the talk of crime. In this paper I discuss Costa Rican crime statistics, their development, and their utilization in the talk of crime against the background of criminological theory. The theses of the paper are that a) the informative value of crime statistics regarding Costa Rican reality is far more questionable than the common utilization of them implies and b) when they are used as argumentation, these crime statistics do not provide evidence of the oft-proclaimed rising crime wave. – – Der costaricanische öffentliche Diskurs über Gewalt und Kriminalität stützt sich wesentlich auf die Prämisse, dass die Kriminalitätsraten in den letzten Jahren in unvergleichlichem Umfang gewachsen seien und heute ein überwältigendes und alarmierendes Ausmaß erreicht hätten. Auf dem Fundament dieser Prämisse wächst in der Bevölkerung die gesellschaftliche Angst und damit der Ruf nach der harten Hand und immer drastischeren staatlichen und privatisierten Maßnahmen der Kriminalitätsbekämpfung. Kriminalitätsstatistiken werden in der Regel als Beleg für die These einer Kriminalitätswelle angeführt. Im öffentlichen Diskurs werden sie aber auf sehr problematische Weise interpretiert. Dieser Beitrag untersucht die offiziellen Kriminalitätsstatistiken, ihre historische Entwicklung und ihren Gebrauch im Diskurs über Gewalt und Kriminalität in Costa Rica anhand kriminologischer Theorie. Die Hypothese ist, dass, erstens, die Aussagekraft der Statistiken über costaricanische Realität weit geringer ist, als ihre übliche Verwendung impliziert, und dass, zweitens, die Statistiken selbst dann die proklamierte Welle des Verbrechens nicht stützen, wenn man sie tatsächlich zugrunde legt.
Keywords: 300; Costa Rica; violence; crime; social order; crime statistics; public discourse